Phenotypic correlations among the amounts of total lean, fat and hone of kıvırcık lamb carcasses and carcass joints - Hıdır Demir (Eurasian Journal of Veterinary Sciences)
This study was earned out to determine the carcass joint to be used most effectively tor the determination ol the amount of total carcass lean, fat and bone. Male Kıvırcık lambs weaned at the age of 75 days and exposed to fatten for 56 days were used in the study. Hot dressing percentage was 46.07% and cold dressing percentage was 45.35% for the lambs slaughtered at the average live weight of 33.45 kg. The highest proportions of joints were 32.63% for leg, 28.26% for other parts and 18.20% for shoulder, respectively. The highest ratio for lean was 61.20% at teg, for fat was 33.00% at loin and for bone was 29.90% at back. The highest phenotypic correlations among the total lean, lat and bone ot the carcass with the lean, fat and bone ot 5 different carcass joints were 0.936 lor lean at leg, 0.734 for fat at loin and 0.823 for bone at other parts. The highest phenotypic correlations between the total carcass lean, fat and bone were with lean, fat and bone of the joint called other parts (0.817. 0.614 and 0.823) and shoulder (0.720, 0.622 and 0.550) and leg (0.936. 0.644, and 0.447) followed this joint.